Wind farms fault ride through using DFIG with new protection scheme - Okedu, K.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (The Institute of Electrical and Electronic Engineers (IEEE), 2012)
This paper proposes a control strategy of doubly fed induction generators (DFIGs) with new protection schemes for enhancing fault ride through capability of wind farms composed of DFIGs and induction generators (IGs). Since the DFIGs will be stressed or overloaded in the process of stabilizing the wind farm during a grid fault, it is paramount to consider a protection scheme for the DFIG, in order to protect its power converters. Two schemes, the dc-link chopper-controlled braking resistor with the supplementary rotor current (SRC) control of the rotor side converter of the DFIG and series dynamic braking resistor (SDBR) connected to the stator of the DFIG, are proposed and compared. Merits and drawbacks of both schemes are highlighted as well. The simulation results in power system computer aided design and electromagnetic transient including DC (PSCAD/EMTDC) show that the two proposed schemes can eliminate the need for an expensive crowbar switch in the rotor circuit, because both could limit the rotor current of the DFIG within its nominal value during a grid fault. Finally, considering the overall system performance, the latter is recommended. © 2012 IEEE.